2005
DOI: 10.1002/jcp.20300
|View full text |Cite
|
Sign up to set email alerts
|

The human polyomavirus BK: Potential role in cancer

Abstract: In human cancer, a role has been suggested for the human polyomavirus BK, primarily associated with tubulointerstitial nephritis and ureteric stenosis in renal transplant recipients, and with hemorrhagic cystitis in bone marrow transplant (BMT) recipients. After the initial infection, primarily unapparent and without clinical signs, the virus disseminates and establishes a persistent infection in the urinary tract and lymphocytes. There is correlative evidence regarding potential role of polyomavirus BK in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 83 publications
0
46
0
3
Order By: Relevance
“…The transforming ability of BKV is thought to be mediated by TAg that binds and inactivates the functions of the products of tumor suppressor genes p53 and pRb. 11,12 This interaction with these particular tumor suppressor proteins disrupts the ability of the cell to regulate cell cycle progression, resulting in uncontrolled proliferation and neoplastic transformation. Recent research has shown that BKV TAg strongly activates the DNA methyltransferase gene.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The transforming ability of BKV is thought to be mediated by TAg that binds and inactivates the functions of the products of tumor suppressor genes p53 and pRb. 11,12 This interaction with these particular tumor suppressor proteins disrupts the ability of the cell to regulate cell cycle progression, resulting in uncontrolled proliferation and neoplastic transformation. Recent research has shown that BKV TAg strongly activates the DNA methyltransferase gene.…”
Section: Case Reportmentioning
confidence: 99%
“…By using the PCR technology, investigators can examine very small biopsy samples for the presence of viral sequences. 11,12,14,15,20 BKV DNA sequences have been reported in a range of human tumors. Our patient was a renal transplant recipient with a previous BKV infection who subsequently developed a transitional cell cancer of the allograft renal pelvis.…”
Section: Case Reportmentioning
confidence: 99%
“…Indeed, similarly to JCV, BKV infects a large percentage of individuals and becomes clinically evident mainly in immunodeficient or immunosuppressed patients (Wang et al, 2004). Equally, BKV DNA has been detected in human tumors, not only of the CNS but also of the pancreas and the urinary tract (Harris et al, 1998a;Croul et al, 2003;Fioriti et al, 2005). BK virus LT-Ag is composed of 695 amino acids and is structurally similar to SV40 and JCV LT-Ag (Figure 1).…”
Section: Bk Virus Large T-agmentioning
confidence: 99%
“…In spite of these numerous studies, the mechanistic role of BKV in human malignancies remains highly debatable. BKV DNA and proteins have been found in renal, bladder, prostate, pancreatic, adrenal, and brain cancer tissues (Corallini et al, 1987;Flaegstad et al, 1999;Fioriti et al, 2005;Barzon et al, 2008;Taghavi et al, 2015;Yin et al, 2015). On the other hand, several reports have failed to detect BKV in similar tumors (Arthur et al, 1994;Weggen et al, 2000;Knöll et al, 2003;Fischetti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%